How is weight teasing cross-sectionally and longitudinally associated with health behaviors and weight status among ethnically/racially and socioeconomically diverse young people? - Laura Hooper; Rebecca Puhl; Marla E. Eisenberg; Marla Reicks; Dianne Neumark-Sztainer (BMC, 2022)
Abstract Background Weight stigma is prevalent among young people and harmful to health. The current study used a health equity lens to examine cross-sectional and longitudinal associations between experiencing weight teasing (a form of weight stigma) with a range of weight-related health behaviors and weight status in an ethnically/racially and socioeconomically diverse sample of young people. We also assessed whether ethnicity/race and adolescent socioeconomic status (SES) operated as effect modifiers in these relationships. Methods Adolescents (n = 1568) were enrolled in EAT 2010-2018 (Eating and Activity over Time) and followed into young adulthood. Weight teasing; screen time; moderate-to-vigorous physical activity (MVPA); sleep duration; breakfast frequency; fruit, vegetable, sugar-sweetened beverage (SSB), and fast-food intake; and body mass index (BMI) were assessed at baseline (mean age = 14.4 years) and eight-year follow-up (mean age = 22.2 years). Multivariate linear regression estimated marginal means and 95% confidence intervals. All analyses adjusted for BMI and sociodemographic characteristics. Results Weight teasing was cross-sectionally associated with longer screen time, shorter sleep duration, and higher BMI during adolescence; and cross-sectionally associated with shorter sleep duration, lower breakfast frequency, higher fast-food intake, higher SSB intake, and higher BMI during young adulthood. In the longitudinal analyses, weight teasing was not associated with health behaviors but did predict higher BMI (teased: 28.2 kg/m2, not teased: 26.4 kg/m2, p < 0.001). White and higher adolescent SES subgroups had higher MVPA, more frequent breakfast intake, lower fast-food intake, and lower BMI than their respective counterparts. The relationships between weight teasing and health behaviors and weight status were largely consistent across ethnic/racial and adolescent SES subgroups. Conclusions Findings add to growing evidence that weight-based mistreatment poses a threat to weight-related health and that young people across ethnic/racial and SES subgroups are vulnerable to the negative effects of weight teasing. Limitations include attrition at follow-up and the self-reported nature of many measures. Results suggest a need for increased attention to existing recommendations to reduce weight stigma in young people from diverse ethnic/racial and socioeconomic backgrounds including training for healthcare providers to better equip them to address the harms of weight teasing and foster more compassionate care to promote health-supporting behaviors in young people.